2016
DOI: 10.1155/2016/8356582
|View full text |Cite
|
Sign up to set email alerts
|

Does Nursery-Based Intensified Anticipatory Guidance Reduce Emergency Department Use for Nonurgent Conditions in the First Month of Life? A Randomized Controlled Trial

Abstract: Objective. We aimed to evaluate the impact of an intensified anticipatory guidance program in the nursery on Emergency Department (ED) use for nonurgent conditions (NUCs) in the neonatal period. Methods. Parturient mothers of healthy newborns were randomized to an intervention group or control group. Baseline and 1-month follow-up knowledge surveys regarding newborn care were conducted. The primary outcome was the proportion of neonates who used the ED for a NUC. Secondary outcome was change in caregivers' kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Alternative methods to educate parents should be considered. 18 In contrast to this outcome, a study by Herman et al, involving a low literacy training intervention by providing a book with basic interventions for common paediatric illnesses resulted in a significant decrease in ED and doctor visits. 19 Similarly, a study by Grant et al examining the effect of a short programme that aimed at providing education on how to deal with common childhood illnesses to parents and advising for review by primary care provider before seeking ED care showed a decrease in NUPs among the study group who received an education.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alternative methods to educate parents should be considered. 18 In contrast to this outcome, a study by Herman et al, involving a low literacy training intervention by providing a book with basic interventions for common paediatric illnesses resulted in a significant decrease in ED and doctor visits. 19 Similarly, a study by Grant et al examining the effect of a short programme that aimed at providing education on how to deal with common childhood illnesses to parents and advising for review by primary care provider before seeking ED care showed a decrease in NUPs among the study group who received an education.…”
Section: Discussionmentioning
confidence: 97%
“…This contrasts with previous studies, which found decreased presentation rates, decreased NUPs and increased admission rates. 17,18,20,21 It would be worthwhile to see whether there is any change in presentations/admission post-Delta variant where the caseloads were much higher than had been seen the year prior. Further studies are warranted to elucidate this.…”
Section: Discussionmentioning
confidence: 99%
“…Support and education for new parents highlighting these potential issues, whilst taking into account factors such as media‐induced fear and access to primary care, are likely to be crucial interventions if this trend is to be reversed 18 . Capitalising on technological advances may be of benefit, with one Internet‐based home monitoring system resulting in reduced neonatal ED attendances, 19 but such community‐based interventions may not always have the expected impact if attitudes towards ED use are not considered 20 …”
Section: Discussionmentioning
confidence: 99%
“…18 Capitalising on technological advances may be of benefit, with one Internet-based home monitoring system resulting in reduced neonatal ED attendances, 19 but such community-based interventions may not always have the expected impact if attitudes towards ED use are not considered. 20 Any policy aimed at appropriate use of non-hospital healthcare resources should focus on some key patient cohorts and ensure the model of care is feasible and acceptable. A larger proportion of neonates in this study were 'well babies' when compared to European cohorts 9,21 though this may reflect literature-based or clinician differences in defining pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Support and education for new parents highlighting these potential issues, while taking into account factors such as media-induced fear and access to primary care, are likely to be crucial interventions if this trend is to be reversed (18). Capitalising on technological advances may be of benefit, with one internet-based home monitoring system resulting in reduced neonatal ED attendances, (19) but such community based interventions may not always have the expected impact if attitudes towards ED use are not considered (20).…”
Section: Discussionmentioning
confidence: 99%